Evaluation of five agricultural information mini-projects in Latin America - Castronovo, Alfonso (IDRC OttawaCA, 1987)
Describes and evaluates five two year mini-projects concerned with agricultural information in Costa Rica, the Dominican Republic, Paraguay, Peru, and Uruguay. Evaluations were made from the points of view of impact, usefulness and efficiency of mechanisms adopted, and type and model of projects. For each project describes production of input, and participation in the AGRIS/AGRINTER system.